2017
DOI: 10.7554/elife.26109
|View full text |Cite
|
Sign up to set email alerts
|

PPP1R15A-mediated dephosphorylation of eIF2α is unaffected by Sephin1 or Guanabenz

Abstract: Dephosphorylation of translation initiation factor 2 (eIF2α) terminates signalling in the mammalian integrated stress response (ISR) and has emerged as a promising target for modifying the course of protein misfolding diseases. The [(o-chlorobenzylidene)amino]guanidines (Guanabenz and Sephin1) have been proposed to exert protective effects against misfolding by interfering with eIF2α-P dephosphorylation through selective disruption of a PP1-PPP1R15A holophosphatase complex. Surprisingly, they proved inert in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 43 publications
12
109
2
Order By: Relevance
“…Several reports, in the context of other diseases, have shown that GA promotes the UPR to counteract ER stress (35,36,39). It has been proposed that GA binds the regulatory subunit of protein phosphatase 1 (PPP1R15A), thereby preventing the dephosphorylation of eiF2α and then protein translation recovery following stress (37, 39), although its exact mechanism of action remains controversial (41,53). Delaying protein translation recovery may thus allow the UPR downstream chaperones (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports, in the context of other diseases, have shown that GA promotes the UPR to counteract ER stress (35,36,39). It has been proposed that GA binds the regulatory subunit of protein phosphatase 1 (PPP1R15A), thereby preventing the dephosphorylation of eiF2α and then protein translation recovery following stress (37, 39), although its exact mechanism of action remains controversial (41,53). Delaying protein translation recovery may thus allow the UPR downstream chaperones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The third pathway is operated by the activating transcription factor 6 (ATF6), a receptor that under ER stress and its dissociation to Grp78 is translocated to the Golgi where it is cleaved to produce a fragment which then acts as a transcription factor to promote expression of XBP1 mRNA and other proteins involved in protein folding. It has been proposed that GA binds to PPP1R15A, thus preventing its binding to PP1c (37,38) and prolonging eIF2α phosphorylation with the effect of reducing the accumulation of misfolded proteins in the ER (37,39), but these data are controversial (40,41).…”
Section: Introduction (700 Words/ 4500 Characters)mentioning
confidence: 99%
“…Recently, the importance of globular actin in the formation of a tripartite holophosphatase complex assembled with GADD34 and PP1c to dephosphorylate eIF2a was revealed (Crespillo-Casado et al, 2017, Chambers et al, 2015, Crespillo-Casado et al, 2018. Given the unusual regulation of eIF2α phosphorylation in DCs, we wondered whether actin organization could also impact this pathway in a different setting than artificial ER-stress induction.…”
Section: Perk and Actin Polymerization Coordinates P-eif2α Levels Andmentioning
confidence: 99%
“…On the other hand, salubrinal (Boyce et al 2005), guanabenz (Tsaytler et al 2011), ISRIB (Sidrauski et al 2015), and Sephin1 (Das et al 2015) can modulate the PERK-induced translational block either up or down by altering eIF2α phosphorylation status (Figure 1). Other explanations for the biological phenotypes induced by guanabenz and Sephin1 may also prove relevant (Crespillo-Casado et al 2017). Notably, these compounds also modulate overlapping aspects of the integrated stress response, rendering such small molecules neither UPR- nor PERK-specific.…”
Section: Targeting the Upr To Modulate Er Proteostasismentioning
confidence: 99%